Gender Representation in Class Ten Nepali Language Textbook - Rana, Nanimaya (Journal of Musikot Campus, 2024)
The present study is based on the analysis of gender representation in textbook. It aims to analyze the situation of gender representation in the texts included in the grade X compulsory Nepali textbook of CDC, GON Nepal. Qualitative framework has been adopted in this study. After an in-depth study of the lessons of the Nepali textbook of grade X, the data has been noted and tabulated. For this, the paradigms created by Logsdon (1985) for the analysis of gender representation have been made a basis. It has been analyzed using the textual method. Out of the seventeen texts included in the textbook of class ten, only one text is written by a female author. In terms of occupation, women are shown only in a limited field compared to men. Examples, contexts and events include a wide range of masculine names and a limited range of feminine names. Overall, it is seen that the textbook is not balanced in terms of gender representation. This study has guided the revision of this book in the future to maintain a balance in it and to pay attention to the role of textbooks in developing the sense of gender equality in children.